Analysis of Palu City Tax Potential and Performance in 2022 - Nuryana Haprin DJ. Achmad*, Nuryana Haprin; Yunus, Santi; Paskua, Meity Ferdiana l; Rahman, Failur (Universitas Syiah Kuala, 2023)
The objectives of this study are as follows: (1) identify the performance of Palu City's regional taxes; (2) map the types of Palu City's regional taxes using the Klassen Typology; (3) identify the potential and problems of regional tax revenue in Palu City; and (4) formulate a strategy to increase regional taxes through intensification and expansion efforts based on the results of the Klassen Typology mapping. While the quantitative method looks at tax performance by using tools for analyzing effectiveness, contribution, and growth rate, as well as the Klassen typology, the qualitative method uses primary data from field surveys with a focus on two types of taxes, namely hotel tax and restaurant tax. A combination of the qualitative and quantitative methods is used to formulate targets in the quantitative method. The findings of quantitative research indicate that the tax performance of the City of Palu for the period spanning 20122020 demonstrates very effective criteria. The percentage value of the Palu City Tax contribution for the period spanning 20122020 demonstrates an average contribution value of 29.9 percent, which is the value of the tax growth rate for the City of Palu during the period spanning 20122020. It is stated that there are two types of Palu City Regional Tax that fall under the underdeveloped criteria. These are the advertising tax and the swallow's nest tax. The year 2020 shows fluctuating values, with the ABT tax having the highest contribution and the swallow's nest tax having the lowest. Based on the Klassen typology analysis, it is stated that there are two types of Palu City Regional Tax that fall under the underdeveloped criteria. According to the findings of qualitative research, land and building taxes have significant tax potential. Furthermore, based on the findings of a survey, it shows that the difference between the potential tax for 2022 and the tax target for 2022 shows the largest figure, which is Rp. 30,877,886,490.